PERILAKU TINDAK TUTUR USTAD DALAM PENGAJIAN: KAJIAN SOSIOPRAGMATIK DENGAN PENDEKATAN BILINGUAL - Sulistyowati, Rini Indah; Prayitno, Harun Joko; Nasucha, Yakub (Universitas Muhammadiyah Surakarta, 2013)
In general, the purpose of this study is to describe the illocutionary speech act of chap- lain using bilingual approach. This is a qualitative research. The data are in the form of speech collected from recordings of cleric K.H. Anwar Zahid from Bojonegoro, East Java as the informant. Data collection techniques used are observation and recording. Data analysis used is equivalent intralingual method aith comparative technique. The results of this study indicate as follows: (a) Assertive modes are expressed in the form of Javanese-Arabic and Arabic-Indonesian; complain mode are in Arabic-Javanese and Arabic-Indonesian); (b) Directive modes are in Arabic-Javanese and Arabic-Indone- sian) and advising modes are in Arabic-Javanese and Arabic-Indonesian); (c) there are commissive mode of offers in Arabic-Javanese and Javanese-Indonesian), (d) Expres- sive congratulation mode in Arabic-Javanese); (e) Declaration form naming mode is in Javanese-Arabic and Arabic-Indonesian. Speech acts used in the teachings are direct speech act, such as to govern, inform or do something directly. The direct speech is used in the form of questions in Arabic-Javaneseand commands Arabic-Javanese and Indo- nesian-Arabic.